2020
DOI: 10.2147/cmar.s246995
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identification of High-Frequency Methylation Sites in RNF180 Promoter Region Affecting Expression and Their Relationship with Prognosis of Gastric Cancer</p>

Abstract: Background: Ring finger protein 180 (RNF180) is a tumor suppressor gene regulated by promoter methylation. We previously demonstrated that the RNF180 promoter methylation could be a risk factor for gastric cancer (GC); and eight high-frequency hypermethylated CpG sites were associated with GC. However, it is not clear whether these key sites can affect gene expression and involve in prognosis. The aim of this study was to investigate the effects of above CpG sites on the gene expression and prognosis of GC. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In hepatocellular carcinoma, RNF180 acts as a tumor suppressor during tumorigenesis (11). RNF180 participates in cell growth and apoptosis, and upregulates not only antiproliferative regulators, but also proapoptotic mediators (12). Thus, RNF180 is associated with invasion and metastasis in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In hepatocellular carcinoma, RNF180 acts as a tumor suppressor during tumorigenesis (11). RNF180 participates in cell growth and apoptosis, and upregulates not only antiproliferative regulators, but also proapoptotic mediators (12). Thus, RNF180 is associated with invasion and metastasis in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Given the ease of sample collection, the detection of DNA methylation in peripheral blood can be used as a molecular biological test for diagnosing disease and predicting patient prognosis, opening a new avenue for noninvasive cancer detection ( 35 , 36 ). There is growing evidence that plasma RNF180 methylation is linked to gastric cancer, and RNF180 methylation has great potential as a diagnostic and prognostic tumor marker, with promising research prospects ( 16 , 37 ). Due to the vulnerability of a single individual clinical study to small sample size, experimental technique, and experimental design ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…When RNF180 was methylated, it led to structural and functional alterations in the gene that made it less effective at promoting apoptosis and failed to stop the growth, differentiation, and metastasis of the tumor (2,(13)(14)(15)(16)(17). Recent clinical studies have demonstrated a strong correlation between the prognosis, overall postoperative survival, lymph node metastases in patients with gastric cancer, and the RNF180 gene methylation status (18)(19)(20)(21). RNF180 methylation was demonstrated by Cheung et al to be detectable in plasma samples from 56.25 (18/32) gastric cancer patients, but not in plasma from 64 healthy controls (11).…”
Section: Introductionmentioning
confidence: 99%
“…GC accounted for 7.7% of total cancer deaths globally in 2020, making it the fourth most common cause of cancer-related deaths[ 12 ]. RNF180 is a tumor suppressor gene involved in many important physiological processes in vivo , such as cell growth, differentiation, and tumorigenesis[ 13 ]. When RNF180 was abnormally expressed, a variety of physical, chemical, and biological factors were affected, resulting in decreased gene expression or corresponding protein dysfunction.…”
Section: Discussionmentioning
confidence: 99%